Comparison of polyvinyl chloride, curved reinforced, and straight reinforced endotracheal tubes for tracheal intubation through Airtraq™ laryngoscope in anesthetized patients - Kush Ashokkumar Goyal; Shaji Mathew; Arun Kumar Handigodu Duggappa; Kanika P Nanda; Souvik Chaudhuri; Renganathan Sockalingam (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: The Airtraq™ video laryngoscope facilitates tracheal intubations in patients with difficult airway or cervical spine immobilization. However, curved reinforced tracheal tube and straight reinforced tracheal tubes are useful where neck of the patient is likely to be moved or flexed or if patient is in prone position, wherein nonreinforced endotracheal tube (ETT) might get kinked and/or compressed. We compared intubation success rate of curved and straight reinforced tracheal tubes with polyvinyl chloride (PVC) tracheal tube using Airtaq™ laryngoscope in paralyzed and anesthetized patients. Material and Methods: Totally, 120 patients underwent random allocation to one of the three groups using computer-generated randomization table. Patients were intubated with appropriate size and type of ETT using Airtraq™ after obtaining optimal glottis view. Experienced anesthesiologist performed endotracheal intubation and unblinded observer noted down success and ease of intubation. Results: Patients intubated with PVC tube (100%) had higher rates of successful intubation and shorter intubation time (4 s), in comparison to intubation with curved reinforced (92.5%) and straight reinforced tubes (SRTs) (85%) using Airtraq™ laryngoscope (AL). However, there was no statistical difference in the incidence of airway trauma among all the three groups. Conclusions: PVC tracheal tube is significantly superior to both curved and SRTs for intubation using AL.